Penggunaan Bahasa Indonesia yang Baik dan Benar dalam Surat Menyurat di Lingkungan Kelurahan se-Kecamatan Lubuk Kilangan Kota Padang - Noviatri Noviatri; Reniwati Reniwati; Aslinda Aslinda (Warta Pengabdian Andalas, 2019)
The dedication of the object of this service is based on the observation of the team regarding the official letter used in the Lubuk Kilangan Subdistrict, Padang City, there are still some mistakes. These errors include the systematic aspects of official letters and the language used in the letter. Therefore, this service aims to provide counseling and training about the systematic letter and the last language of letters that are good and right. There were several stages of the method applied in this activity, namely the counseling phase, the training phase, and the evaluation phase. In the counseling phase, the types of letters, systemic letters, and the format of the letters are explained. At the training stage, each administrative staff in charge of the correspondence in the Lubuk Kilangan Subdistrict of Padang City was given the task of training to make or draft several official letters. In the third stage, an evaluation is carried out. After the evaluation, the results showed that staff who participated in training and outreach activities were aware and acknowledged that there had been many errors in writing official letters, especially regarding the language of the letters. After participating in this counseling, the staff had good knowledge of the systematics and language of letters.